A Study of Potato Peel Extract (Solanum Tuberosum L) as a Green Corrosion Inhibitor on Low Carbon Steel in a 3.5% NaCl Environment - Nugroho, Firman A.; Soedarsono, Johny Wahyuadi (invotek, 2023)
Wide application in the oil and gas industry made carbon steel suffer annual losses due to corrosion. The corrosion protection utilizes inhibitor have drawbacks expensive and harmful to the environment. Potato peel extract (solanum tuberosum L) and its main constituents, such as flavonoids, alkaloids, and tannins, have been investigated as a green corrosion inhibitor for low-carbon steel in a 3.5% NaCl solution. The inhibitor’s effectiveness and corrosion rate monitoring were measured using weight loss. Potentiodynamic polarization was used to investigate the type of corrosion inhibition and adsorption of plant extract on the surface. Fourier transform infrared spectroscopy (FTIR) was utilized to observe the presence of functional groups, natural compounds, and the type of bonding for adsorbed organic inhibitors on the surface. The results of the Tafel polarization analysis indicated that the potato peel extract acts as a mixed-type inhibitor. The inhibition efficiency increased with the concentration of the inhibitor extract. The optimal inhibition efficiency of 73.33% is was achieved with 6 ml of potato peel extract and 216 hours of immersion time. The inhibitive effect is due to the adsorption of inhibitor molecules on the steel surface, following the Langmuir adsorption isotherm.